Characteristics of the Fungal Communities and Co-occurrence Networks in Hazelnut Tree Root Endospheres and Rhizosphere Soil - Ma, Wenxu; Yang, Zhen; Liang, Lisong; Ma, Qinghua; Wang, Guixi; Zhao, Tiantian (Frontiers in Plant Science, 2021)
Hazelnut has gained economic value in China in recent years, but its large-scale planting and research started later than other countries. Conducting basic research on hazelnut trees requires studying their related microorganisms. Here, we used high-throughput DNA sequencing to quantify the fungal communities in the root endospheres and rhizosphere soil of four hazelnut species. Fungal diversity in the rhizosphere soil was significantly higher than that in the root endospheres. Rhizosphere soil had more Mortierellomycota, and the fungal community compositions differed among the four hazelnut species. The root endospheres, especially those of the Ping’ou (Corylus heterophylla × Corylus avellana) trees, contained more ectomycorrhizal fungi. The co-occurrence networks in the rhizosphere soil were more sophisticated and stable than those in the root endospheres, even when the root endospheres had higher modularity, because the structural differentiation of the root endospheres differed from that of the rhizosphere soil. Two-factor correlation network analysis and linear regression analysis showed that the total organic carbon was the main environmental factor affecting the fungal communities. Our study revealed the community compositions, functional predictions, and co-occurrence network structural characteristics of fungi in hazelnut root endospheres and rhizosphere soil. We also examined the potential keystone taxa, and analyzed the environmental factors of the dominant fungal community compositions. This study provides guidance for the growth of hazelnut and the management of hazelnut garden, and provides an insight for future development of fungal inoculants to be used in hazelnut root.